Kajian Literatur Mengenai Subrogasi, Restorno, Endorsement, dan Klausula Pada Polis Asuransi Syariah - Utari, Diana Putri; Widyaningtias, Anabilla Alma; Aslamiyah, Tsuwaebatul; Joni Joni; Fauziah, Raihani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine in depth the relationship between subrogation, restorno, endorsement, and clauses in sharia insurance policies, by reviewing their suitability based on the commercial law perspective contained in the Commercial Law Code (KUHD) and the principles of Islamic law that form the basis for the implementation of sharia insurance in Indonesia. The research also focuses on analyzing how these four elements are interrelated in forming a legal and operational structure for sharia insurance policies that is fair, transparent, and in accordance with sharia values. The research method used is descriptive qualitative with a library research approach, which collects data from various literature sources, such as books, journals, and regulations related to sharia insurance. The results of the study show that these four elements complement each other in forming the legal and operational structure of sharia insurance policies. Clauses form the basis of the agreement, endorsements serve to accommodate changes, subrogation maintains the sustainability of tabarru' funds, and restorno reflects fairness in the distribution of surpluses. The implementation of these elements must be in accordance with sharia principles, positive law, and DSN-MUI fatwas in order to create a fair, transparent, and sustainable insurance system.